1998 International Zurich Seminar on Broadband Communications. Accessing, Transmission, Networking. Proceedings (Cat. No.98TH82
DOI: 10.1109/izsbc.1998.670249
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of contention resolution algorithms for a cable modem MAC protocol

Abstract: A reservation-based MAC protocol has been adopted by standards bodies as the basic protocol for data communication within the upstream channel of a cable plant. The available capacity is divided in two separate channels. One is a random access channel, or contention channel, used to send requests to the head-end, with the possibility of collisions occurring therein. When collisions happen, they are resolved by using a Contention Resolution Algorithm (CRA). The second channel is a data channel to send user info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Over the past years, different technologies have appeared in which a contention period is defined to request the needed resources by the different nodes of the system, being developed some studies, like [4], [5] in HFC (Hybrid Fiber Coaxial), and [6], [7] in cable modem. An overview and comparison of contention resolution algorithm are shown in the latter papers.…”
Section: Related Workmentioning
confidence: 99%
“…Over the past years, different technologies have appeared in which a contention period is defined to request the needed resources by the different nodes of the system, being developed some studies, like [4], [5] in HFC (Hybrid Fiber Coaxial), and [6], [7] in cable modem. An overview and comparison of contention resolution algorithm are shown in the latter papers.…”
Section: Related Workmentioning
confidence: 99%
“…The blocked binary-tree algorithm has been widely used in the shared networking like ALOHA and satellite communications [3] and has been introduced in HFC network research as shown in [4] [5]. It is applied as the CRA mechanism in this paper due to its simplicity and high resolution efficiency.…”
Section: Fig 4 the Diagram Of Binary Tree Cramentioning
confidence: 99%
“…Since an m-ary tree scheme was introduced [1, 6,14], a number of variants have been reported [9,12]. Also, a ternary tree scheme was adopted in IEEE 802.14 HFC standard [3,13,15]. In general, an m-ary tree scheme requires the feedback information about the result of data delivery attempt.…”
Section: Introductionmentioning
confidence: 99%